Designing for mobile participation in blended higher educational settings - Jaldemark, Jimmy; Lindberg, Ola (Proceedings of the International Conference on Networked Learning, 2014)
As society is increasingly dependent on mobile technological solutions, higher education needs to be prepared for changing behaviours in terms of increasingly emerging mobile communication patterns of students and teachers. Therefore, projects that explore models of mobile participation in blended higher education settings are needed. This paper concerns the design for participation in mobile learning and in particular how participation could be designed into educational settings. Focus in the paper is the design of a university project aimed at exploring models of participation in blended learning through the use of mobile learning. The project "Mid Sweden University and Mobile Learning (MUML)" is used in the paper as an example of such design. This is argued to be of strategic value for institutions of higher education, the need to be up-to-date with the development within the mobile society. A wide range of learning about mobile learning in higher education settings were built into the project, including conducting research reviews and diverse experiences from teachers. The project included trials that were conducted in four different first-cycle programs, which then informed the planning and conducting of further trials in courses. These trials included approaches to mobile applications and devices that embraced the deployment of university-owned equipment as well as bring-your-own-device scenarios. Cumulative features were included in the design of the project with the purpose of informing the performance of features in later stages of the project. Iterations were included to create loops of different features that could help participants recycle and share their experiences. In this way the project had the intentions to explore different forms of participation.